Dietary Habit And Nutritional Status In Forcibly Displaced Myanmar National Adolescents - Chowdhury, Monzur Al Murshed; Islam, ANM Shamsul; Simi, Nur Jahan; Rahman, Md Raziur (Journal of Preventive and Social Medicine, 2024)
Background: Adolescence is a unique intervention point in the life-cycle for a number of reasons. Malnutrition is an important cause of adolescent morbidity & growth retardation. Appropriate feeding practice, hygiene and sanitation can reduce these consequences through maintenance of nutrition and prevention of infection. Methods: A cross sectional study was carried out among 268 respondents in 5, 8, 8w,18 camp situated in Ukhiya upazila, Cox’s Bazar. Data were collected by convenient sampling through face to face interview using semi-structured questionnaire. Data were analyzed by SPSS 25 software. Results: The study found that highest number (37.7%) of the respondents were in age group of 16 to 19 years. Majority (75.7%) respondent have formal education up to primary school. Drinking water were 100% tube well water, living house were 100% kacha. Majority of the adolescents (87%) were unmarried, 58.2% had family size of 4-6 person, 95.1% were unemployed. Most (67%) of the respondents had thinness (underweight) and 7% adolescents had severe thinness (underweight). According to z-score, 23% and 7% were severely stunted. According to Food Consumption Score, 69.9% of the respondents had borderline consumption and 19.7% had poor consumption. Only 1.2% of the respondents went to bed hungry due to shortage of food. Chi-square test showed statistically significant relationship was found between nutritional status and age of the respondents (p<0.05), but no significant relationship was found between nutritional status and sex of the respondents (p>0.05). Conclusion: Although undernutrition was found in the most of the aspects, attention could be given to improve balanced diet, improve accommodation facilities, availability of safe drinking water, availability of education for all FDMNs living in the camp to improve overall nutritional status. JOPSOM 2021; 41(2):50-56